BLOOMSBYNFI / Nurul Farisya Irwayu Mohd Izwan - Mohd Izwan, Nurul Farisya Irwayu (2021)
The business that I have created to sale a product based on food and services. The main objectives that I want to achieve for the business is to offer variety of food and dessert that can make people satisfied and happy with our products from all over Malaysia and hoping that one day will go more further in the future. This business was started on 24 th November 2020. Our business offer with affordable price to our customer by giving them a different flavour with different range of prices. There are many people that sell food and dessert in social media platform. We want to sell our product that people can buy and afford and taste the differences between other desserts. The name of the business was chosen because it easy to remember and simple for everyone to reads it.